Characterization of mineral phosphate solubilizing and plant growth promoting bacteria from termite soil of arid region - Chakdar, Hillol; Dastager, Syed G.; Khire, Jayant M.; Rane, Digeshwar; Dharne, Mahesh S. (3 Biotech, 2018)
Five highly efficient phosphate solubilizing bacteria, viz., Pantoea sp. A3, Pantoea sp. A34, Kosakonia sp. A37, Kosakonia sp. B7 and Bacillus sp. AH9 were isolated from termitorial soils of Sanjivani island of southern Maharashtra, India. These isolates were characterized and explored for phosphate solubilization and plant growth promotion. Among these, Bacillus sp. AH9 showed highest phosphate solubilization index (3.5) and solubilization efficiency (250%) on Pikovskaya agar. Interestingly, Pantoea sp. A34 displayed maximum mineral phosphate solubilization (1072.35mg/L) in liquid medium and during this period the pH dropped to 3.13. All five isolates had highest P solubilization at 48h after inoculation. During mineral phosphate solubilization, both gluconic acid and 2-keto gluconic acid were produced by Kosakonia and Bacillus isolates, while only 2-keto gluconic acid was detected in Pantoea isolates. Highest organic acid (39.07 +/- 0.04g/L) production was envisaged in Bacillus sp. AH9, while Pantoea sp. A34 produced the least amount (13.00 +/- 0.01g/L) of organic acid. Seed bacterization with Pantoea sp. A3 and Kosakonia sp. A37 resulted in 37% and 53% increase in root length of tomato seedlings, respectively, while Pantoea sp. A34 and Kosakonia sp. B7 had deleterious effects on root length as well as overall growth of the seedlings. To our knowledge, this is the first report of plant growth promoting potential of microorganisms isolated from termitorial soil of Sanjivani island, which is a drought-prone area. Therefore, such efficient growth promoting P solubilizers can offer an effective solution for sustainable agriculture in arid, dryland farming and drought-prone regions.

Development of low-cost plant probiotic formulations of functional endophytes for sustainable cultivation of Coleus forskohlii - Mastan, Anthati; Rane, Digeshwar; Dastager, Syed; VivekBabu, C. S. (Microbiological Research, 2019)
Deployment of plant endophytes at field level is reported to make an impact on agricultural crop productivity; development and deployment of suitable crop specific plant probiotics in a suitable delivery matrix is a value-added task. In our study, we attempted to develop bioformulations of native, fungal endophytes of Coleus forskohlii to improve plant yield using two different carrier-based materials (talc and wheat bran). Initially, fungal endophytes (RF1, SF1, and SF2) were grown on sterilized wheat bran under solid state condition and their growth kinetics and pattern were analyzed by ergosterol content and scanning electron microscope, respectively. 10-day-grown fungal endophytic cultures were used for the development of two types of formulations (wheat bran and talc-based formulations) and tested for their efficacy on host plant, C. forskohlii under field conditions. Interestingly, application of wheat bran-based endophytic formulations significantly (p < 0.01) enhanced plant height (12-29%), number of branches (51-63%), root biomass (26-33%), photosynthetic pigments (32-101%), and forskolin content (35-56%) compared to talc-based formulations under field conditions. Shelf life of endophytes (RF1, SF1, and SF2) in both formulations revealed spore viability in wheat bran-based formulations for 6 months storage period as compared to talc-based formulations. Overall, the present investigation envisages developing plant probiotic bioformulations of functional endophytes of C. forskohlii to enhance root biomass and in planta forskolin content.

Plant probiotic bacterial endophyte, alcaligenes faecalis, modulates plant growth and forskolin biosynthesis incoleus forskohlii - Mastan, Anthati; Rane, Digeshwar; Dastager, Syed G.; Vivek Babu, Chikkarasanahalli Shivegowda (Probiotics and Antimicrobial Proteins, 2020)
Coleus forskohliiis an herb, well-known for its medicinal compound forskolin present in its roots, with wide range of pharmaceutical applications. Here, we report, for the first time, the role of plant-probiotic bacterial endophytes ofC. forskohlii, CFLB1 and CFRB1, isolated from leaf and root, which regulate plant growth andin plantforskolin content. Native bacterial endophyte, CFRB1 (Alcaligenes faecalis), significantly modulates primary plant productivity and forskolin content under pot and field conditions. Under field conditions, CFRB1 endophyte application significantly enhanced photosynthetic pigments and reduced the severity of root-knot and root rot diseases. Expression analyses of functional genes involved in the forskolin biosynthesis inC. forskohliiplants treated with CFRB1 endophyte under field conditions revealed differential upregulation of fourC. forskohliiditerpene synthases (CfTPSs),CfTPS1,CfTPS2,CfTPS3andCfTPS4, along with cytochrome P450 (CfCYP76AH15) and acyltransferase (CfACT1-8) genes. CFRB1 treatment reduced the severity of nematode infection and root rot inC. forskohliiplants by 81 and 78%, respectively. Overall, we demonstrate that cross-talk of plant-endophyte interaction inC. forskohliiis beneficial, leading to enhanced forskolin content through modulation of forskolin biosynthetic pathway genes along with increased plant yield and reduced disease incidence. Thus, endophytic isolate,A. faecalis(CFRB1), could be deployed as a novel bio-stimulant for enhancingin plantaforskolin content during cultivation ofC. forskohlii.
Keywords: Alcaligenes faecalis; CfACT1-8; CfCYP76AH15; CfTPSs; Coleus forskohlii; Forskolin; Plant-probiotic bacterial endophyte

Molecular insights of fungal endophyte co-inoculation with Trichoderma viride for the augmentation of forskolin biosynthesis in Coleus forskohlii - Mastan, Anthati; Rane, Digeshwar; Dastager, Syed G.; Babu, C. S. Vivek (Phytochemistry, 2021)
To understand the compatibility of three native endophytic fungi Phialemoniopsis cornearis (SF1), Macrophomina pseudophaseolina (SF2) and Fusarium redolens (RF1) with Trichoderma viride (TV1) on Coleus forskohlii in enhancing plant growth and forskolin content, field experiments were conducted. Co-inoculation of RF1+TV1 showed significant improvement in plant growth (52%), root biomass (67%), and in planter forskolin content (94%), followed by treatment with SF2+TV1 and SF1+TV1. qRT-PCR was carried out to quantify expression of five key forskolin biosynthetic pathway genes (CfTPS2, CfTPS3, CfTPS4, CfCYP76AH15, and CfACT1-8) in RF1+TV1 treated C. forskohlii plants. Elevated expression of CfTPS2, CfTPS4, CfCYP76AH15 and CfACT1-8 genes was observed with RF1+TV1 combination as compared to uninoculated C. forskohlii plants. Besides, RF1+TV1 treatment considerably reduced the severity of nematode infection of C. forskohlii plants under field conditions. Thus, congruent properties of F. redolens (RF1) were witnessed with co-inoculation of T. viride (TV1) under field conditions which resulted in enhanced forskolin content, root biomass, and reduced nematode infections in C. forskohlii. Overall, this approach could be an economical and sustainable step towards cultivation of commercially important medicinal plants.
Keywords: Co-inoculation; Coleus forskohlii; endophytes; Forskolin; Lamiaceae; Trichoderma viride